Modulation by metformin of molecular and histopathological alterations in the lung of cigarette smoke‐exposed mice. (28th March 2014) - Izzotti, Alberto; Balansky, Roumen; D'Agostini, Francesco; Longobardi, Mariagrazia; Cartiglia, Cristina; Micale, Rosanna T.; La Maestra, Sebastiano; Camoirano, Anna; Ganchev, Gancho; Iltcheva, Marietta; Steele, Vernon E.; De Flora, Silvio
Abstract The anti‐diabetic drug metformin is endowed with anti‐cancer properties. Epidemiological and experimental studies, however, did not provide univocal results regarding its role in pulmonary carcinogenesis. We used Swiss H mice of both genders in order to detect early molecular alterations and tumors induced by mainstream cigarette smoke. Based on a subchronic toxicity study, oral metformin was used at a dose of 800 mg/kg diet, which is 3.2 times higher than the therapeutic dose in humans. Exposure of mice to smoke for 4 months, starting at birth, induced a systemic clastogenic damage, formation of DNA adducts, oxidative DNA damage, and extensive downregulation of microRNAs in lung after 10 weeks. Preneoplastic lesions were detectable after 7.5 months in both lung and urinary tract along with lung tumors, both benign and malignant. Modulation by metformin of 42 of 1281 pulmonary microRNAs in smoke‐free mice highlighted a variety of mechanisms, including modulation of AMPK, stress response, inflammation, NFκB, Tlr9, Tgf, p53, cell cycle, apoptosis, antioxidant pathways, Ras, Myc, Dicer, angiogenesis, stem cell recruitment, and angiogenesis. In smoke‐exposed mice, metformin considerably decreased DNA adduct levels and oxidative DNA damage, and normalized the expression of several microRNAs. It did not prevent smoke‐induced lung tumors but inhibited preneoplastic lesions in both lung and kidney. In conclusion, metformin was able to protect the mouse lung from smoke‐induced DNA and microRNA alterations and to inhibit preneoplastic lesions in lung and kidney but failed to prevent lung adenomas and malignant tumors induced by this complex mixture.